Preliminary evaluation of a novel, fully automated, Telenostic device for rapid field-diagnosis of cattle parasites. Issue 11 (24th September 2020) - Elghryani, Nagwa; Crispell, Joseph; Ebrahimi, Roohollah; Krivoruchko, Michael; Lobaskin, Vladimir; McOwan, Trish; O'Connor, William; Power, Eamonn; Voisin, Bruno; Scholz, Dimitri; de Waal, Theo
Abstract: New ideas for diagnostics in clinical parasitology are needed to overcome some of the difficulties experienced in the widespread adoption of detection methods for gastrointestinal parasites in livestock. Here we provide an initial evaluation of the performance of a newly developed automated device (Telenostic) to identify and quantify parasitic elements in fecal samples. This study compared the Telenostic device with the McMaster and Mini-FLOTAC for counting of strongyle eggs in a fecal sample. Three bovine fecal samples were examined, in triplicate, on each of the three fecal egg-counting devices. In addition, both manual (laboratory technician) and automated analysis (image analysis algorithm) were performed on the Telenostic device to calculate fecal egg counts (FEC). Overall, there were consistent egg counts reported across the three devices and calculation methods. The Telenostic device compared very favourably to the Mini-FLOTAC and McMaster. Only in sample C, a significant difference ( P < 0.05) was observed between the egg counts obtained by Mini-FLOTAC and by the other methods. From this limited dataset it can be concluded that the Telenostic-automated test is comparable to currently used benchmark FEC methods, while improving the workflow, test turn-around time and not requiring trained laboratory personnel to operate or interpret the results.